Correction to: Infuence of real-world cue exposure and mood states on drinking: testing neurobiological models of alcohol use disorder. - Meredith, Lindsay R.; Baskerville, Wave-Ananda; Lee, Carrie; Grodin, Erica N.; Wassum, Kate M.; Ray, Lara A. (Psychopharmacology, 2025)
The article addresses a correction made to a previously published paper in the field of psychopharmacology, specifically regarding the name of the second author. The correct last name is now stated as Baskerville, omitting the erroneous addition of "Mann." The publisher, Springer Nature, emphasizes its neutrality concerning jurisdictional claims in published maps and institutional affiliations. This correction ensures the accuracy of authorship in the academic record.